Gold complexes and their molecular targets in colorectal cancer - Raahilah, Zahir Essa; Brianna *,; Yeo, Chien Ing *; Teow, Sin-Yeang (Elsevier, 2024)
Even with the advent of various treatment modalities, colorectal cancer (CRC) remains one of the leading causes of cancer morbidity and mortality worldwide. A widely used treatment for metastatic CRC—platinum-based chemotherapy—is hampered by the lack of selectivity, inducing adverse side effects in patients, and the emergence of drug resistance, severely limiting their therapeutic efficacy. To overcome these limitations, researchers are exploring the potential of gold complexes as a promising alternative to treat CRC. Gold complexes have demonstrated potent anticancer activity, particularly through the inhibition of thioredoxin reductase (TrxR), an antioxidant enzyme that is often upregulated in solid tumor cancers such as CRC. Herein, this review provides an overview of CRC and discusses the recent advances of gold complexes along with their modes of action in targeting CRC cells.